2019
DOI: 10.1111/ejh.13316
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of minimally important differences and responder definitions for EORTC QLQ‐MY20 scores in multiple myeloma patients

Abstract: Objectives: Thresholds for the minimally important difference (MID) or responder definition (RD) in health-related quality-of-life (HRQoL) scores are required to interpret the impact of an intervention or change in the trajectory of the condition which is meaningful to patients. This study aimed to establish MID and RD for the European Organisation for Research and Treatment of Cancer Quality of Life Multiple Myeloma questionnaire (EORTC QLQ-MY20).Methods: A novel mixed-methods approach was applied by utilizin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 32 publications
1
23
0
Order By: Relevance
“…Nonetheless, many of the subgroup differences seen on the EORTC QLQ-C30 questionnaire approached or exceeded the ≥6 points considered to represent clinically meaningful differences. [30][31][32] Likewise, some of the changes observed on the QLQ-MY20 tool also exceeded those proposed to represent clinically meaningful differences (10 points for Disease Symptoms and Side Effects of Treatment, 13 points for Body Image, and 9 points for Future Perspectives). 32 Our data highlight the considerable negative impact of MM on patient HRQoL.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Nonetheless, many of the subgroup differences seen on the EORTC QLQ-C30 questionnaire approached or exceeded the ≥6 points considered to represent clinically meaningful differences. [30][31][32] Likewise, some of the changes observed on the QLQ-MY20 tool also exceeded those proposed to represent clinically meaningful differences (10 points for Disease Symptoms and Side Effects of Treatment, 13 points for Body Image, and 9 points for Future Perspectives). 32 Our data highlight the considerable negative impact of MM on patient HRQoL.…”
Section: Discussionmentioning
confidence: 96%
“…[30][31][32] Likewise, some of the changes observed on the QLQ-MY20 tool also exceeded those proposed to represent clinically meaningful differences (10 points for Disease Symptoms and Side Effects of Treatment, 13 points for Body Image, and 9 points for Future Perspectives). 32 Our data highlight the considerable negative impact of MM on patient HRQoL. A recent global study including 15,386 people from the general population reported normative HRQoL data for the EORTC QLQ-C30 questionnaire; 33 mean (SD) GHS/QoL scores were 66.1 (21.7) overall and 67.0 (21.8) for German participants.…”
Section: Discussionmentioning
confidence: 96%
“…However, the present study adopted a triangulation process, which has been recently recommended by a group of authors, to establish recommended thresholds for further references (Coon & Cappelleri, 2016). It was often observed that the magnitude of within‐patient change (MIC) was generally greater than that of between‐group difference (MID) (Sully et al., 2019). The present results, however, showed that the values of MIC and MID of studied measures are relatively comparable.…”
Section: Discussionmentioning
confidence: 99%
“…This study will provide estimates of means/SD for the intended outcomes of a fully powered RCT, to support a sample size calculation for a larger trial. Meaningful clinically important differences are known for a number of the secondary end points, including the FACIT-F,44 EORTC-QLQ-30 and MY20 module45 46 and 6MWT47 and will be used to inform future sample size calculations. For a pilot study, including >30 participants in each arm is considered to be an acceptable number 48 49…”
Section: Methods and Analysismentioning
confidence: 99%